Adaptation to Space Debris Mitigation Guidelines and Space Law. Issue 1 (2nd January 2017) - Rajapaksa, Chandana Rohitha; Wijerathna, Jagath K.
ABSTRACT: Space exploration is a mechanism whereby, with the use of astronomy and space technology, humans are able to explore outer space and the universe at large. In this article, the authors address space debris issues with a discussion of future space law issues along with a brief elaboration of how the adaptation took place for space debris mitigation guidelines. The history of space law formulated during the United Nations' General Assembly is justified, along with the resolutions that took place throughout recent years. The authors also elaborate on the importance of theoretical modeling and how it could be adopted into practice utilizing the established debris mitigation guidelines. Legal and political constraints are also highlighted, along with where the future focus on legal factors should be when considering space debris mitigation.